CHANGES IN THE LIFE OF THE MAIN CHARACTER AS A PERSON WITH ASPERGER’S SYNDROME IN KATHRYN ERSKINE’S MOCKINGBIRD - Anisa Asri; Ni Made Widisanti S; Tetty Yukesti (Universitas Pakuan, 2020)
The main topic in this research is changes in the main character as a person with Asperger's syndrome in Kathryn Erskine’s Mockingbird. The process of this research involves the whole story, intrinsic elements: character and characterization, conflict, and setting. This qualitative research is supported by descriptive analysis method and library research technique that shows the main character as a person with Asperger's syndrome can experience character changes even though the research states that person with this syndrome is quite difficult to progress in terms of social interaction. A person with asperger syndrome has a persistent nature, but gradually the main character is able to pass through all the processes of change in her life. Keywords: character changes; asperger syndrome; main character.